Analisis Penerapan Teori Belajar Kognitif Melalui Metode Ceramah dan Tanya Jawab dalam Pembelajaran PAI Kelas V di SDIT Insan Mulia Surakarta : Penelitian - Muhammad Hanan Mufti; Amalia Putri Iqbal; Bunga Mustaqim; Liza Anastya Sabilla; Fatima Nur Rahmadhani; Praptiningsih Praptiningsih (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to analyze the utilization of ZEP Quiz digital media in Informatics learning based on the Merdeka Curriculum at SMP Islam Nurussalam Al Khoir. The main focus of the research is to examine how the use of ZEP Quiz can enhance students’ motivation, participation, and learning outcomes in student-centered learning. This study employs a descriptive qualitative approach involving one Informatics teacher and twenty-three eighth-grade students as research subjects. Data were collected through observation and in-depth interviews, then analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results indicate that ZEP Quiz is able to create an interactive and enjoyable learning environment, increase student engagement, and assist teachers in conducting real-time assessment of learning outcomes. Supporting factors include teacher readiness, school facility support, and continuous evaluation. Meanwhile, the obstacles encountered relate to limited devices and internet connectivity. This study contributes to the development of digital learning practices aligned with the principles of the Merdeka Curriculum and supports the formation of adaptive and digitally literate learners.